FAKTOR – FAKTOR YANG MEMPENGARUHI PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN BANYUASIN - Dwi Septa Aryani; N Nabilah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
This research aims to examine factors affecting the regional state-income (PAD). Regional state-income is an income earned and collected by the regional state in accord with the regulations. Local tax, local retribution, and other revenues are some factors affecting the regional state-income of Banyuasin district that are employed in this study. The source of data used in this research is secondary data. Time-series data is used in this study which spans 6 years period (2010 to 2015). Descriptive analysis and multivariate regression are employed to analysis the data. The result reveals that (1) local tax, local retribution, and other revenues have a positive and significant effect on regional state-income simultaneously; (2) local tax, local retribution, and other revenues have a positive and significant effect on regional state-income partially. Keyword: Regional State-Income, Local Tax, Local Retribution, Other Revenues.